The incorporation of 3H-palmitic acid into Ornithogalum umbellatum lipotubuloids, which are a cytoplasmic domain rich in lipid bodies and microtubules. Light and EM autoradiography - Maria Kwiatkowska (Acta Societatis Botanicorum Poloniae, 2011)
In the ovary epidermis of Ornithogalum umbellatum L. lipotubuloids were found, i.e. distinguished cytoplasmic domain with an agglomeration of half unit membrane-surrounded lipid bodies, entwined and held together by a system of microtubules (Protoplasma 75: 345-357; 77: 473-476).